Unjuk Kerja Evaporator Pada Mesin Pendingin Dengan Siklus Adsorpsi Menggunakan Energi Surya - Amusadar, Amusadar; Hasbi, Muhammad; Samhuddin, Samhuddin (ENTHALPY, 2021)
Energy needs in Indonesia continue to increase every year. The largest use of energy is in the industrial sector, where its needs reach 42.12% of the total national energy needs. To save energy, energy saving measures are needed in the industrial sector so that the increase in energy demand can be restrained. So we conducted research on the performance of the evaporator in a refrigeration machine with an adsorption cycle using solar energy. The purpose of this study was to determine the working process of the evaporator with activated carbon refrigeration and to determine the efficiency of the evaporator in the activated carbon pair adsorption refrigeration system. This research was conducted by observing and recording the evaporator temperature of the refrigeration machine every hour. The results of the research in three days of testing, namely, on the first day the highest evaporator temperature increase was at 16.00 o'clock, which was 33.2 oC and the lowest evaporator temperature was at 07.00 o'clock, which was 25.1 oC. On the second day, the highest increase in evaporator temperature was at 16.00, which was 32.2 oC and the lowest evaporator temperature was at 07.00, which was 23.8 oC. On the third day, the highest increase in evaporator temperature was at 36.4 oC and the lowest evaporator temperature was at 06.00, which was 24.5 oC. Kata kunci: Adsorption, evaporator, temperature